(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
One of the most pressing tasks of the modern university is the implementation of a competency-based approach in the field of education. This approach involves the formation of key competencies, skills to adapt to the reality around us, a world in which globalization trends are rapidly developing, implying the international division of labor and the dominance of information technology. The problem of enhancing students’ learning is one of the most pressing issues of pedagogical science and practice. This article discusses about the implementation of the principle of activity in learning which has great importance, because learning and development are activity-based in nature and the results of training and education of the students directly depend on the quality of learning as an activity.